PENGARUH INFLASI DAN KURS TERHADAP INVESTASI DI PROVINSI SUMATERA UTARA PADA TAHUN 2001-2022 - GRESIA SEPTINA SITOHANG; Muhammad Aldi Akbar; FEROZI RAMDANA IRSYAD; ANGELINA ROLAS OLIVIA NAIBAHO; JONATAN MARBUN; FILJA AZKIAH SIREGAR; JOKO SUHARIANTO (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
North Sumatra is one of the provinces in Indonesia that has significant investment potential. There are numerous factors that deeply influence investment within the region. One vital component in driving the economic growth of a country is investment, which is crucial for increasing employment opportunities and income for the residents of North Sumatra Province. However, in recent years, the investment level in North Sumatra has experienced fluctuations. One suspected root cause of these fluctuations is the inflation rate and exchange rate. The research methodology employed in this study involves collecting data on inflation and exchange rates occurring in North Sumatra Province over a specified period. Subsequently, the data will be quantitatively analyzed using multiple linear regression method with the assistance of statistical data processing tool Eviews 9, yielding an R-squared value of 0.83. In other words, the inflation and exchange rate variables contribute 83% to the investment level in North Sumatra Province, with an additional 17% of variance not accounted for in this study. The research findings indicate that the exchange rate has a positive and significant impact, while inflation has a negative and significant impact on investment in North Sumatra Province during the period from 2001 to 2022. Keywords: Investment, Exchange Rate, Inflation, North Sumatra